2014
DOI: 10.3367/ufne.0184.201405e.0510
|View full text |Cite
|
Sign up to set email alerts
|

High-energy neutrino astronomy: a glimpse of the promised land

Abstract: In 2012, physicists and astronomers celebrated the hundredth anniversary of the detection of cosmic rays by Viktor Hess. One year later, in 2013, there was first evidence for extraterrestrial highenergy neutrinos, i.e. for a signal which may contain key information on the origin of cosmic rays. That evidence is provided by data taken with the IceCube neutrino telescope at the South Pole. First concepts to build a detector of this kind have been discussed at the 1973 International Cosmic Ray Conference. Nobody … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…New similar gamma-ray flares of the same blazar in 2016 were not accompanied by neutrino excesses at IceCube; this, however, does not contradict the predictions of the proposed models [98]. It was this observation by AMANDA which motivated [4] the development of a system of mutual neutrino and gamma-ray telescope alerts, which has been actively developing already in the IceCube era.…”
Section: Search For Flaresmentioning
confidence: 72%
See 2 more Smart Citations
“…New similar gamma-ray flares of the same blazar in 2016 were not accompanied by neutrino excesses at IceCube; this, however, does not contradict the predictions of the proposed models [98]. It was this observation by AMANDA which motivated [4] the development of a system of mutual neutrino and gamma-ray telescope alerts, which has been actively developing already in the IceCube era.…”
Section: Search For Flaresmentioning
confidence: 72%
“…It is not the purpose of this review to discuss in detail the history of neutrino astronomy, nor to give a detailed technical description of the instruments at work, see Refs. [2,4,5] and references therein. Brief information about past, present, and emerging detectors, which may be useful in reading the rest of the review, can be found in Table 2.…”
Section: Past Present and Future Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the key reliability factor of neutrino astrophysics is the unification of the efforts of different experiments, which use different methods and have different sensitivities to the Northern and Southern skies. Since 2013, these efforts are being developed [82,83] within the framework of the Global Neutrino Network 3 (GNN). Probably, the creation of focused thematic working groups, which would include representatives of different experiments, will allow one to advance much further in understanding astrophysical neutrino sources.…”
Section: Fight For Accuracy: Detectors In Liquid Watermentioning
confidence: 99%